2020
DOI: 10.31410/tmt.2020.301
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Tourist Potential in Serbia in the Light of Tourist Frequency and Accommodation Capacities

Abstract: In the last several decades, tourism registers continuous growth on the global level. The subject of analysis of this paper is the ratio of the number of arrivals and overnight stays of tourists in general, as well as the number of arrivals and overnight stays of tourists by regions for the chosen three-year period 2017-2019. Also, this paper establishes and analyses both the total and quantitative indicators of the accommodation capacities by regions, also for the chosen reference three-year period. The last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In one study conducted on a sample of 320 elderly respondents in Serbia, it was shown that the favorite travel destinations are spas and mountains and that the main motive is rest and improving health, while proximity to the destination and travel costs are the most important factors in the process of choosing a destination (Spasojević and Božić, 2016). When it comes to domestic tourists, the most visited destinations are Šumadija and Western Serbia, while the most visited destination for foreign tourists is the Belgrade city (Počuča and Matijašević, 2020). Certainly, the pandemic of Covid-19 had a meaningful influence when it comes to choosing destinations because the large number of tourists from Serbia turned to domestic destinations due to the uncertainty of the situation.…”
Section: Introductionmentioning
confidence: 99%
“…In one study conducted on a sample of 320 elderly respondents in Serbia, it was shown that the favorite travel destinations are spas and mountains and that the main motive is rest and improving health, while proximity to the destination and travel costs are the most important factors in the process of choosing a destination (Spasojević and Božić, 2016). When it comes to domestic tourists, the most visited destinations are Šumadija and Western Serbia, while the most visited destination for foreign tourists is the Belgrade city (Počuča and Matijašević, 2020). Certainly, the pandemic of Covid-19 had a meaningful influence when it comes to choosing destinations because the large number of tourists from Serbia turned to domestic destinations due to the uncertainty of the situation.…”
Section: Introductionmentioning
confidence: 99%